READING BHAGAVAD-GῙTĀ BUILDING RESILIENCE AND ABILITY TO GET OUT OF SUFFERING - Ni Luh Arick Istriyanti (Veda Jyotih: Jurnal Agama dan Sains, 2022)
Literacy of the Hindu scriptures, namely Bhagavad-gῑtā, is proven to be able to build resilience and the ability to get out of suffering. This study measures the Resilience and Coping Strategy of Bhagavad-gῑtā readers in Bali. The results showed that the motive and frequency in reading Bhagavad Gita together played a role in resilience. The results showed that the the Bhagavad-gῑtā readers’ resilience was influenced by 41.5% by the motive (the inner desire to read Bhagavad-gῑtā) and the frequency of reading Bhagavad-gῑtā. Apart from that, the coping strategy are also valuable for Bhagavad-gῑtā readers. The Resilient and Coping strategy together have a massive role for individuals to survive and even find a way out during difficulties due to the COVID-19 pandemic. This notion also proves that literacy has real impacts on its readers, such as building strength, endurance and ability to get out of crisis. In addition, suicide is not an option in a crisis, as many people do.